STUDY OF PRODUCT QUALITY ASPECTS, PRICES AND HALAL LABELS ON THE PURCHASE DECISION OF HPAI HERBAL PRODUCTS - Erdawati, Erdawati; Asraf, Asraf; Elondri, Elondri; Yuliza, Mai (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
For reasons of protecting Indonesian Muslim consumers, the Government has regulated the guarantee of halal products by including Halal Labels on each product packaging. However, only 10% of the products on the market have included the Halal Label. Indonesian society, which is predominantly Muslim and reaches 229 million people, should be a potential market for products labeled Halal. There are a number of companies that specifically only market halal products and make the Halal label and product quality as an underdog factor. This study reveals how the influence of product quality, price and Halal label on consumer decisions to buy HPAI products that specifically market Halal products. Based on the Lemeshow formula, the respondents were determined as 96 people from consumers who use HPAI products in Indonesia. The regression analysis conducted shows that product quality and halal labels each influence purchasing decisions, while price does not have a significant effect. This shows that the strategy for product quality and Halal labels implemented by HPAI is correct, so it needs to be maximized as well as a reference for other Halal product manufacturers in increasing their marketing. Because the level of competition between similar products is not too tight, then the price is not a determining factor in the decision. However, price remains a sensitive factor when the level of competition is already high. Keywords: Product Quality, Price, Halal Label and Purchase Decision.